Development and validation of HPLC methodology for quantitative estimation of Efinaconazole in topical pharmaceutical formulation prepared in‐house for the treatment of onychomycosis. Issue 9 (23rd July 2020) - Patani, Nikesh; Patel, Mrunali; Patel, Rashmin
Abstract: The purpose of this research work was to design, develop, and optimize new high‐performance liquid chromatography method for quantitative estimation of Efinaconazole in topical pharmaceutical formulation developed in‐house for the treatment of onychomycosis. Based on the outcomes of preliminary investigation, optimized high‐performance liquid chromatography conditions were reverse phase column (Luna C18) as stationary material, with simple isocratic mobile phase comprising mixture of water and acetonitrile (20:80 v/v), flow rate 1 mL/min, column oven temperature 30°C, injection volume 10 µL, detection wavelength of 230 nm, and total run time of 10 min. The optimized method was successfully validated as per International Council for Harmonization guideline Q2(R1), and statistical analysis proved that the method is specific (peak purity ≥ 0.999), accurate (99.21–99.63% w/w), precise (% relative standard deviation < 2.0), and sensitive (limit of detection = 9.26 µg and limit of quantitation = 28.05 µg). As a result, this research work provides a new and simple high‐performance liquid chromatography methodology with optimized chromatographic parameters for quantitation of Efinaconazole as a routine assay purpose, contributing to the technological and scientific domain and guaranteeing a safe and effective use of Efinaconazole for the treatment of onychomycosis.